P131 REVEALING THE ERGONOMIC CRISIS OF AN UPPER GASTROINTESTINAL ROBOTIC SURGEON – STILL A LOT TO IMPROVE IN MINIMALLY INVASIVE SURGERY. (23rd November 2019) - Fuchs, H; Ahn, F; Leers, J; Schröder, W; Höfler, C; Bruns, C
Abstract: Introduction/Aim: Minimally invasive technologies have improved outcomes after esophagectomy and the use of robotic technology in Europe is rapidly increasing. Even though robotic technology was primarily developed to improve perioperative outcomes, many robotic surgeons complain about ergonomics when using existing devices. Aim of this study is to evaluate the ergonomics of the newest robotic technology in a center of excellence for upper gastrointestinal surgery. Background and Methods: Starting 02/2017 the latest available robotic system (davinci xi) was introduced at our academic center (certified center of excellence for surgery of the upper gastrointestinal tract, n>300 esophageal cases/year). Surgeons ergonomics were studied using a standardized video capture and touch sensor protocol (Fig 1 & 2). Data recorded were analyzed to study whether the new robotic system was used in an ergonomic fashion throughout robotic esophageal surgery. Results: From 02/2017 – 05/2019, a total of 90 mainly upper gastrointestinal robotic cases including 45 Esophagectomies for cancer and 25 Heller Myotomies were performed. All cases were performed safely without operation-associated intraoperative complications. Even though experienced robotic console surgeons used the robotic device, the davinci xi arm rest was used in less than 25% of surgery time (Fig. 3), resulting in loss of efficacy when using the robotic range of motion. Video documentation using the new technology is provided to showcase the dilemma. Conclusion: Robotic technology allows for safe minimally invasive upper gastrointestinal surgery. Further development in robotics should focus on improvement of surgeons ergonomics.